"Mn" Incorporated Coconut Water Derived Carbon for Supercapacitor Application. (8th September 2021) - Nakate, Yogesh T.; Nakate, Umesh T.; Salunke, Rahul; Mane, R. S.; Shirale, Dhammanand J.
Abstract : Carbon derived from natural precursors is attracting tremendous attention from the scientific community for high-performance supercapacitor applications. This is for the first time; one-step synthesis was carried out for Mn incorporated carbon derived from coconut water as the starting precursor via the spray pyrolysis method. An energy-efficient, low-cost, and eco-friendly method of synthesis is a need of time. Three different concentrations (0.08 M, 0.05 M, and 0.02 M) of "Mn" incorporated carbon were prepared and tested for supercapacitor application. Among these, 0.05 M Mn incorporated coconut water carbon (Mn/CWC) manifests the highest areal capacitance of 438.33 mF cm −2 at the current density of 2 mA cm −2 with the energy density of 21.91 × 10 −3 Wh cm −2 and 299.9.18 × 10 −3 W cm −2 power density and shown 94.8% of capacitance retention rate at the current density of 4 mA cm −2 after the 2000 cycles. The results indicated that 0.05 M Mn incorporated CWC can be a potential candidate for electrode material in energy storage applications.